(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2014)
Cities are complex systems, but they are incomplete systems. All cities are becoming the same, but all cities are competing with each other. Here actors from different worlds meet, but there are no clear rules of engagement. It is in this context that the complex global city becomes a frontier space with political consequences. Here we can find new hybrid bases from which to act, spaces where the powerless can make history even when they do not get empowered.